Natural product as a source of prodrug - Padmavathy, Jagannathan; Devarajan, Saravanan (Bangladesh Journal of Pharmacology, 2017)
The natural products are the chemical constituents that are generated from the living organism. The natural products are isolated from the plants, animals, and microorganisms which are used in drug design and drug discovery. Natural product is then modified by chemical synthesis as either total or semi-synthetic way. The natural products show various pharmacological activity which can be used for the treatment of a variety of diseases. Natural products could be regarded as a source of quantifiable and chemically pure known products and also natural products can be utilized as complex mixtures subjected to chemical variability. The present review article adds up the prodrugs from natural products as well as prodrugs developed from the natural products.